Routledge handbook on capital punishment - Bohm, Robert M.; Lee, Gavin (Routledge handbooks, 2018)
Capital punishment : history, opinion, and culture -- The American death penalty : a short (but long) history / John Bessler, University of Baltimore School of Law -- Capital punishment and lynching / Margaret Vandiver, University of Memphis -- Punishement -- Public opinion about the death penalty / James D. Unnever, University of South Florida, Sarasota, Manatee; Leah Butler, University of Cincinnati; Francis Cullen, University of Cincinnati; and Angela Thielo, University of Louisville -- The marshall hypotheses / John Cochran, University of South Florida -- Culture -- Media and capital punishment / Matthew Robinson, Appalachian State University -- Popular media and the death penalty : a critical discourse analysis of the death penalty in film / Maya Pagni Barak, University of Michigan - Dearborn -- Why we need the death penalty / Andrew Fulkerson, Southeastern Missouri State University -- Capital punishment : rationales and religious views -- Rationales -- Retribution / George Kain, Western Connecticut State University and Dale Recinella, St. Mary Mother of Mercy -- General deterrence and brutalization / Gennaro Vito, University of Louisville and Anthony Vito, University of West Georgia -- Incapacitation and life without parole / Jon Sorensen, Texas A&M University, Prairie View and Thomas Reidy, ABPP -- Religious views -- Christianity and the death penalty / Tobias Winright, St. Louis University -- Judaism and the death penalty / Edna Erez, University of Illinois at Chicago and Kathy Laster, Victoria University -- Death penalty in Sharia law / Sanaz Alasti, Lamar University and Eric Bronson, Lamar University -- Capital punishment and constitutional issues -- The U.S. supreme court and the death penalty / Katherine Bennett, Armstrong State University and H. Chris Tecklenberg, Armstrong State University -- Capital punishment and aggravating and mitigating circumstances / Carol Steiker, Harvard Law School and Jordan Steiker, University of Texas Law School -- Capital offenders' intellectual disability and "insanity" : excluding and delaying the death penalty / Peggy Tobolowsky, University of North Texas -- The death penalty's administration -- The financial costs of the death penalty : examining the evidence / Gordon Waldo, Florida State University -- Prosecutors and capital punishment / Stacy Parker, Muskingum University -- Counsel for the despised and condemned : capital defense attorneys / Jeffrey Kirchmeier, City University of New York School of Law -- The capital jury and sentencing: neither guided nor individualized / Wanda Foglia, Rowan University and Marla Sandys, Indiana University Bloomington -- The penalty phase of the capital murder trial : a social-psychological analysis / Mark Costanzo, Claremont McKenna College and Zoey Costanzo, Cornell University -- The appellate process in capital cases / Vanessa Woodward Griffin, University of West Georgia and O. Hayden Griffin III, University of Alabama, Birmingham -- Clemency : failsafe or fantasy? / Cathleen Burnett, University of Missouri - Kansas City -- Execution methods in a nutshell / Deborah Denno, Fordham University -- California's chaotic death penalty / Stacy Mallicoat, California State University, Fullerton; Brenda L. Vogel, California State University, Long Beach; and David Crawford, Death Penalty Focus -- Reflections on the abattoir - Texas / Dennis Longmire, Sam Houston State University and Alex Updegrove, Sam Houston State University -- The federal death penalty / Stephanie Mizrahi, California State University, Sacramento -- The death penalty and the United States armed forces / Catherine Grosso, Michigan State University -- The death penalty's consequences -- The topography of capital punishment : geographic variations in seeking, achieving, and carrying out the death penalty / Adam Trahan, University of North Texas; Kaleigh B. Laird, University of North Texas; and Douglas N. Evans, Mercy College -- Age, class, and sex disparities in capital punishment / Etta Morgan, Jackson State University -- Race and the death penalty / Kristie Blevins, Eastern Kentucky University and Kevin Minor, Eastern Kentucky University -- Wrongful capital convictions / Talia Roitberg Harmon, Niagara University and Diana Falco, Niagara University -- Life and work on death row / Robert Johnson, American University -- Capital punishment and victims' and offenders' families / Lynn Pazzani, University of West Georgia -- Capital punishment's co-victims / Kyle Burgason, Iowa State University -- Exoneration: life after death row / Scott Vollum, University of Minnesota, Duluth -- The demise of the death penalty with special focus on the United States / Robert M. Bohm, University of Central Florida -- Index